Patrimonial education in school, with school and beyond school: a conversation with teachers in dialogue with Paulo Freire (Cadernos de Sociomuseologia, 2022)
The aim of this text is to conduct a dialogue with teachers about heritage education in the so-called formal environment of education, without neglecting to consider the potential of its relationship with the non-formal envrironment of education. Thefore, the debate starts from the guidelines of heritage education established by the Ordinance/Iphan nr. 137/2016, which are described and detailed, demonstrating how the thinking of the educator Paulo Freire permeates and influences the concept of heritage education established by the Historical and Artistic National Heritage Institute, in Brazil. The argumentative path points in the sense that the detailed guidelines defend a heritage education based on a dialogical, reflective and critical perspective, with the effective participation of communities and people. Following the teachings of Paulo Freire’s work, heritage education must assume its political dimension that takes into account, in a horizontal and democratic way, the different knowledges, perspectives and cosmovisions regarding cultural heritage and its preservation processes.Keywords: Heritage education; Paulo Freire; heritage; memory